When breath becomes air - Kalanithi, Paul (New York : Random House, 2016)
A memoir by a young neurosurgeon faced with a terminal cancer diagnosis who attempts to answer the question, "what makes a life worth living?"
Keywords: Kalanithi, Paul -- Health; Lungs -- Cancer -- Patients -- United States -- Biography; Neurosurgeons -- Biography; Married people -- Biography